Estudo in vitro da atividade citotóxica de naftoquinonas inéditas e a relação com espécies reativas de oxigênio em linhagem de células de câncer de pulmão - Lyra Junior, Paulo Cilas Morais (2013)
Lung Cancer (LC) represents a challenge to the world health care, setting as the leading cause of cancer among men and women showing a difficult therapy to be a heterogeneous disease. Knowing that, new searches for chemotherapeutic agents more effective is imperative in order to reduce the deaths from this fellness that effects people into the worldwide. Thus, all attention is turning to new agents from natural origin, by reason of being found in nature easily and therefore and having a low cost price. The interest in the group of naphthoquinones that makes part of the quinines arises because it has a natural origin and can be found widely in nature. Naphthoquinone has associate several action mechanisms that can cause cytotoxicity to the cells. Among the action mechanisms proposed for the naphthoquinones is the increase of reactive oxygen species (ROS) into the microenvironment. The ROS are naturally into living organisms, however when they become markedly elevated there is an occurrence of redox-imbalance in the cell and it becomes associated to the cells death. Having an interest of developing an alternative therapy to patients affected with LC, our group, in partnership with a Research Laboratory of Organic Chemistry, analyzed two unheard naphthoquinones compounds – PIC20 and PIC21 – in line of LC – H460 in order to check the citotoxicity of the new tested compounds, and also evaluate if is happening an citotoxicity profile change of the tested compounds related to ROS present in the tumor microenvironment. We could noticed that PIC20 and PIC21 has citotoxicity effects in line of LC – H460 and the citotoxicity may be related to the presence of ROS (superoxide and hydrogen peroxide), since the treatment with each compound that is associated to superoxide dismutase that changed the profile of the cell viability